2015
DOI: 10.1039/c5ra11415b
|View full text |Cite
|
Sign up to set email alerts
|

Strain and structure order variation of pure aluminum due to helium irradiation

Abstract: Mechanisms were proposed to interpret strain changes and phase transformation caused by the ordered crystal structure being broken under He+ irradiation of 1060 pure aluminum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These defects would affect the integrity of the crystal structure and induce lattice distortion and stress in irradiated samples. The phenomenon can be revealed by the X-ray diffraction patterns of un-irradiated and irradiated samples that are given in [16]. It can be seen that the (111) peak intensity of the irradiated sample is lower than that of an un-irradiated sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These defects would affect the integrity of the crystal structure and induce lattice distortion and stress in irradiated samples. The phenomenon can be revealed by the X-ray diffraction patterns of un-irradiated and irradiated samples that are given in [16]. It can be seen that the (111) peak intensity of the irradiated sample is lower than that of an un-irradiated sample.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were previously grounded with an increasing mesh number of SiC sandpapers (from 180 to 1000), finishing with a diamond-alcohol solution polishing compound polish to make a mirror finish. Afterwards, a beam of helium ions (10 µA•cm −2 , 50 keV) were perpendicularly injected into the surface of the target by a MT3-R ion implanter (Beijing BoRuiTianCheng Technology Co., Ltd., Beijing, China) at 300 • C. In [16], a schematic diagram of the home-made MT3-R ion implanter was given. An initial thinning of the samples to sheets with thickness less than 0.1 mm was made by removing materials from the sample undersurface using SiC sandpapers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the substrate, the surface morphology of TA3 implanted with Nb ions appears smoother, while some small pits appear on the metal surface. Studies have suggested that some pits are formed on the surface due to the bombardment and cascade collisions caused by high-energy ion implantation [18,19]. Additionally, the etching effect produced during the continuous bombardment of TA3 with Nb ions reduces the relative height of the surface bulge, which explains the flattening of surface morphology [20].…”
Section: Surface Structure and Morphologymentioning
confidence: 99%
“…in fusion materials, which may affect the properties of the materials. [3][4][5][6][7] Furthermore, a great many helium atoms derived from (n, a) transmutation reactions will accumulate in the rst wall material and the approximate atomic concentration of helium atoms may reach up to 1.0% (10 000 appm) at the end of the envisaged life of the rst wall material. 1 It is widely known that helium atoms are almost insoluble in iron and they may be trapped in iron through two types of mechanism.…”
Section: Introductionmentioning
confidence: 99%